Towards a combined prognostic index for survival in HIV infection: the role of 'non-HIV' biomarkers. - Justice, Amy C; McGinnis, K A; Skanderson, M; Chang, C C; Gibert, C L; Goetz, M B; Rimland, D; Rodriguez-Barradas, M C; Oursler, K K; Brown, S T; Braithwaite, R S; May, M; et al. (HIV medicine, 2010)
As those with HIV infection live longer, 'non-AIDS' condition associated with immunodeficiency and chronic inflammation are more common. We ask whether 'non-HIV' biomarkers improve differentiation of mortality risk among individuals initiating combination antiretroviral therapy (cART).
Keywords: Aged; AIDS-Related Opportunistic Infections; Anemia; Anti-HIV Agents; Biological Markers; Cause of Death; CD4 Lymphocyte Count; Cohort Studies; Confidence Intervals; Disease Progression; Drug Therapy, Combination; Female; Hepatitis, Viral, Human; HIV Infections; HIV Long-Term Survivors; Humans; Liver Cirrhosis; Male; Middle Aged; RNA, Viral; Severity of Illness Index; Substance-Related Disorders; Survival Analysis